Ethical Challenges for an Understanding of Suffering: Voluntary Stopping of Eating and Drinking and the Wish to Hasten Death in Advanced Patients - Rodríguez-Prat, Andrea; Monforte-Royo, Cristina; Balaguer, Albert (Frontiers in Pharmacology, 2018)
Some persons with advanced disease but no significant cognitive impairments consciously decide to stop taking food and fluids orally, even though they remain physically able to do so. The question is to what extent voluntarily stopping eating and drinking (VSED) may be considered an expression of a wish to hasten death, in the sense that the latter has been defined recently. We analyze the data reported in some studies in relation to primary care patients who died as a result of VSED and examine their results in light of the qualitative findings of patients that expressed a wish to die. In our view, VSED can be understood as a response to physical/psychological/spiritual suffering, as an expression of a loss of self, a desire to live but not in this way, a way of ending suffering, and as a kind of control over one’s life. Thus, VSED is consistent with the wish to hasten death. Prior to interpreting this act as a deliberate expression of personal autonomy, it is important to explore all possible areas of suffering, including physical symptoms, psychological distress, existential suffering and social aspects. Failure to do so will mean that we run the risk of abandoning a fellow human being to his or her suffering.